Agribusiness Development Strategy through Diversification: Dealing with Dynamic Markets - Tri Waluyo (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2023)
Market dynamics in the agribusiness sector require an innovative and adaptive approach so that business actors can remain competitive and sustainable. This research aims to investigate and analyze agribusiness development strategies through product diversification as an effort to deal with dynamic markets. This research uses a qualitative approach with descriptive methods. The research results show that the agribusiness development strategy through product diversification is able to have a positive impact. Careful market analysis enables the identification of potential products that match consumer needs and available resources. Encouragement of innovation and following the latest research helps improve product quality, while partnerships with related industry players support wider market access. Effective marketing, with a deep understanding of the added value of products and the use of attractive branding, is the key to increasing product appeal in a dynamic market. Overall, agribusiness diversification strategies are proven to provide growth and sustainability opportunities, help agribusinesses overcome market challenges, and improve their competitive position in the agricultural industry.